Contesting corporate responsibility in the Bangladesh garment industry: the local factory owner perspective - Fontana, Enrico; Dawkins, Cedric (SAGE, 2024)
In the developing economy of Bangladesh, local factory owners in the garment industry have felt great pressure to improve factory safety, but the costs for those improvements are not shared by the global apparel firms that wield immense influence over them. Consequently, we examine whether multi-stakeholder initiatives (MSIs), as vehicles of corporate social responsibility (CSR), offer platforms for democratic oversight or merely serve as new arenas to exercise corporate power. Given their role in connecting global and local contexts and their history of safety incidents, local factory owners possess a unique perspective on the impact and contested nature of CSR in global supply chains. This article presents a qualitative study of MSIs in the Bangladesh garment industry, particularly after the Rana Plaza collapse. Through interviews with local factory owners and executive managers, we explore the reasons behind their opposition to CSR as exercised by global apparel firms, and the contestation of those practices by their local business association. Our findings lead us to conclude that garment industry MSIs are unlikely to be effective without labor procurement practices that harmonize global and local interests to mitigate the competitive pressures on local factory owners.
Keywords: Bangladesh garment industry; contested governance; corporate social responsibility (CSR); local suppliers; multi-stakeholder initiatives (MSIs); supply chain governance